1998
DOI: 10.1021/ma980694k
|View full text |Cite
|
Sign up to set email alerts
|

Termination, Isomerization, and Propagation Reactions during Ethene Polymerization Catalyzed by Cp2Zr−R+ and Cp*2Zr−R+. An Experimental and Theoretical Investigation

Abstract: Ethene polymerization in toluene has been studied in the temperature range -7 to +97°C and pressure range 0.28 to 9 bar, using two different L 2ZrCl2/methylaluminoxane (MAO) catalyst systems. With bis(cyclopentadienyl)zirconium dichloride (Cp2ZrCl2, L ) Cp), the average activity over 1 h increases with temperature between 10 and 97°C. With bis(pentamethylcyclopentadienyl)zirconium dichloride (Cp*2ZrCl2, L ) Cp*), a maximum average activity over 1 h is observed at 45°C. If propagation and deactivation effects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
142
2

Year Published

1999
1999
2002
2002

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 110 publications
(167 citation statements)
references
References 44 publications
(117 reference statements)
23
142
2
Order By: Relevance
“…The effects were extremely distinct with (n-BuCp) 2 OH bond very easily because the chain transfer to ethene dominates. This hypothesis is supported by a molecular modeling study 16 of two catalysts in which the formation of the Zr ϩ OH bond was highly endothermic when chain transfer to ethene dominated and less endothermic when ␤-H elimination was the major termination mechanism. By way of analogy, the hydrogen probably would be inserted more easily on the active site that forms Zr ϩ OH bonds.…”
Section: Influence Of Hydrogenmentioning
confidence: 81%
“…The effects were extremely distinct with (n-BuCp) 2 OH bond very easily because the chain transfer to ethene dominates. This hypothesis is supported by a molecular modeling study 16 of two catalysts in which the formation of the Zr ϩ OH bond was highly endothermic when chain transfer to ethene dominated and less endothermic when ␤-H elimination was the major termination mechanism. By way of analogy, the hydrogen probably would be inserted more easily on the active site that forms Zr ϩ OH bonds.…”
Section: Influence Of Hydrogenmentioning
confidence: 81%
“…44 We, therefore, expected a dependency between the polymer molecular weight and the amount of free TMA. To test this, a commercial MAO solution was dried to remove free TMA, and solutions of MAO with known amounts of TMA were prepared.…”
Section: Polymerization With Cp* 2 Zrclmentioning
confidence: 93%
“…From our previous work, we have found that the influence of TMA on polymerization and resulting polymer properties is catalyst-specific. 44 Furthermore, it has not been clear whether TMA is free or complexed to MAO and whether it acts by modifying the MAO structure or acts alone or in concert with MAO.…”
Section: Polymerization With Cp* 2 Zrclmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical calculations convincingly demonstrate the existence of ␤-agostic interactions in various [(C 5 H 5 ) 2 Zr-R] ϩ complexes, although the reasons for a stronger agostic interaction of the ␤-CH 3 group vs. the ␤-CH 2 group we propose are not clear. [32][33][34][35] Scheme 3 shows the major steps of ethylene polymerization reactions under this assumption. Most of the reactions in this scheme are the same as those in Schemes 1 and 2.…”
Section: A Strongly Agostic Co Complex [Cpco-mentioning
confidence: 99%